Methods of Using Media Technologies in Organizing Laboratory Trainings in Zoology Sciences - Tulkinovna, Khonnazarova Mamlakat (European Journal of Life Safety and Stability (2660-9630), 2022)
This article has been about methods of using media technologies in organizing laboratory trainings in zoology sciences. The concept of methods is widely used in scientific circles in our country. In addition, Uzbek alternatives such as method and style, teaching way are used side by side with it. A method is a method used to achieve a goal. In fact, we use it in every field, every second, in our daily life. The use of media technologies as a method in laboratory training in the teaching of zoology is a means of acquiring new knowledge in the field of science. Methods are widely understood as a collection of countless methods used in teaching processes. The use of various forms of media technologies as a method in zoology laboratory activities is to achieve creative thinking through the analysis of various processes.